PENGARUH MODEL PEMBELAJARAN RESOLUSI KONFLIK BERBASIS CARTOON DIGITAL (PRK-CD) TERHADAP KEMAMPUAN RESOLUSI KONFLIK SISWA KELAS IV SDN 025 CIKUTRA BANDUNG - Daffa Wahid Prasetyo; Yona Wahyuningsih; Agus Mulyana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of the Digital Cartoon-Based Conflict Resolution Learning Model (PRK-CD) on the conflict resolution skills of fourth-grade students at SDN 025 Cikutra Bandung. A quantitative approach was employed using a True Experiment method with a Pretest-Posttest Group Design. The research sample consisted of 25 fourth-grade students selected through Cluster Random Assignment. Data collection utilized a self-rating scale questionnaire measuring 9 dimensions of conflict resolution skills. The results of hypothesis testing using a Paired Sample T-Test proved that there is a highly significant effect of implementing the PRK-CD Model (Sig. value 0.000 < 0.05). Based on the N-Gain analysis, students achieved a score of 0.68, classified in the medium-to-high category. These findings indicate that the PRK-CD Model is effective in improving students’ conflict resolution skills in an urban school environment, particularly through conflict scenarios relevant to students’ daily interactions in dense classrooms.